Overview Profile of High Sensitive Troponin I (hsTnI) Levels Based on Infarction Location in Acute Myocardial Infarction Patients: A Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Hafni, Noer; Rismawati Yaswir; Desywar (HM Publisher, 2024)
Background: Acute myocardial infarction (AMI) remains an important health problem globally. A diagnosis of AMI can be made by finding at least two of the three criteria, namely typical angina pain, electrocardiography (ECG) abnormalities, and increased cardiac biomarkers. Variations in troponin levels based on examination time and infarct location were obtained from previous studies. High-sensitive troponin I (hsTnI) is a very specific biomarker in detecting myocardial damage. This study aims to determine the description of hsTnI levels based on the location of the infarction in AMI patients of Dr. M. Djamil General Hospital Padang. The location of the infarction in AMI determines the management and prognosis for the clinician. Methods: This research is a retrospective study with a cross-sectional design at the Laboratory Installation of Dr. M. Djamil General Hospital Padang. The sample was adult patients diagnosed with AMI with complete data that met the inclusion and exclusion criteria, taken from medical records. Results: This study showed that from a total of 140 AMI patients, 67 samples met the inclusion criteria. A total of 67 AMI patients consisted of 59 men (88.06%) and 8 women (11.94%) with an average age of 60.1 + 10.5 years. The highest hsTnI levels were found at the posterior infarction location, 40,000 ng/L (16,639-48,997). The location of the infarction was dominated by the inferior infarction location in 20 people (29.9%). Conclusion: The highest hsTnI levels were found at the posterior infarction location. The location of the infarction is dominated by the inferior infarction location in AMI patients with ST elevation at Dr. M. Djamil General Hospital Padang.